Numerical Analysis and Optimization of Design Parameters of a Plate Heat Exchanger using Different Fluids - Rath, Subhasisa; Sikata Samantaray, Dr. (International Journal of Engineering and Technology, 2018)
The main purpose of this work is to examine the effect of design factors on the heat transfer and hydraulic performance of the plate-heat exchanger. Also to use Taguchi optimization technique to optimize the design parameters for maximization of heat transfer rate and minimization of pressure drop. A numerical analysis of plate heat exchanger (PHE) using different fluids (i.e. milk, orange juice and water) is presented in this paper by using COMSOL Multiphysics. The different fluid systems which are considered for this present study are case-1 (milk-water), case-2 (orange juice-water) and case-3 (water-water). Different models are built by varying the design parameters of the plate heat exchanger. In this present study, 600 chevron angle corrugated plates are considered. The different design parameters which are taken for this study are, length of the plates (L), space between each plate (S), amplitude of corrugation on the plate (A) and pitch of corrugation on the plate (P). L16 orthogonal array system of Design of experiments (DOE) is adopted to conduct the numerical analysis. From various models, the influence of design parameters on the performance of plate- heat exchanger for all the fluids are studied. The results of all the three cases are also presented in this paper. Also, in this paper, an attempt is made to optimize the design parameters by using Taguchi optimization technique, in order to minimize the pressure- drop and maximize the rate of heat transfer to The Taguchi optimum setting design parameters for heat transfer coefficient for case-1 (Milk-water) is found to be Length= 32 cm, Space= 0.5 cm, Amplitude= 0.3 cm and Pitch= 0.65 cm and for pressure drop is found to be Length= 28 cm, Space= 0.2 cm, Amplitude= 0.6 cm, Pitch= 0.65 cm. In the process industry like fruit juice processing or milk pasteurization, in order to maximize the heat transfer and minimize the pressure drop during processing, optimum sized plate heat exchanger should be used. The present work will provide the optimum geometrical parameter of the plates to achieve desired output for different inlet temperatures.Â Â